Planning and market relations - Kaser, Michael Charles; Portes, Richard; The International Economic Association (London : Macmillan ; New York : St Martin's Press, 1971)
This is the report of the Conference of the International Economic Association held at Liblice, Czechoslovakia in May, 1970. It was financed under subsidies from UNESCO, Ford Foundation, and by services provided by the Czechoslovakia Academy of Sciences.
Proceedings of a conference held by the International Economic Association at Liblice, Czechoslovakia.
Includes bibliographical references and index..
rpm 01/11/2017
Loans
Keywords: Economic policy